Combination of biological and hydrothermal pretreatment of mixed rice biomass for fermentable sugar production - Ang, Kian Thing (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Mixed rice biomass (combination of rice straw and rice husk) is one of the most staple agricultural by-products in Malaysia. Generally for every 1 kg of paddy grain harvested about 11.5 kg of the rice straw and 200 g of the rice husk are obtained. In this study, mixed rice biomass which combines rice husk and rice straw in certain ratio, was used to synthesize fermentable sugars. The mixed rice biomass was physically pretreated using grinder and it was being sieved. White-rot fungus strain Phanerochaete chrysosporium was used for the biological pretreatment at 30 oC for 7 days. Lignin content in lignocellulosic was removed during biological pretreatment. The autohydrolysis pretreatment was used to remove hemicellulose. Reducing sugar content of soluble mixed rice after autohydrolysis process was determined by 0.225 g sugar/g sample. Characteristic of raw and solid pretreated mixed rice biomass had been observed by Scanning Electron Microscopy (SEM) and functional groups were determined by Fourier Transformed Infrared (FTIR). Based on the result, the characterization analyses of the raw and pretreated sample illustrated significant physical changes of the mixed rice biomass after biological and antohydrolysis pretreatment. In order to maximize the production of fermentable sugar, two parameters which are concentration of commercial cellulase enzyme used, Celluclast 1.5L and incubation time were optimized using Response Surface Methodology (RSM). Based on processed software, 13 runs with different condition were performed to observe the condition for highest yield of reducing sugar. It was discovered that fermentable sugars production was increased from 0.098 g sugar/g sample (0.125 g/L) to 0.248 g sugar/g sample (0.319 g/L) at 81.94 hours incubation time and 10 FPU/g enzyme concentrations in optimization on conditions of enzymatic saccharification. Hence, the total reducing sugar produced was calculated as 0.473 g sugar/g sample and saccharification was determined as 69.78%.